The Optical Biopsy. Issue 4 (October 2015) - Kennedy, Gregory T.; Okusanya, Olugbenga T.; Keating, Jane J.; Heitjan, Daniel F.; Deshpande, Charuhas; Litzky, Leslie A.; Albelda, Steven M.; Drebin, Jeffrey A.; Nie, Shuming; Low, Philip S.; Singhal, Sunil
<x xml:space="preserve">Abstract</x> Background: With increasing use of chest computed tomography scans, indeterminate pulmonary nodules are frequently detected as an incidental finding and present a diagnostic challenge. Tissue biopsy followed by histological review and immunohistochemistry is the gold standard to obtain a diagnosis and the most common malignant finding is a primary lung adenocarcinoma. Our objective was to determine whether an intraoperative optical biopsy (molecular imaging) may provide an alternative approach for determining if a pulmonary nodule is a primary lung adenocarcinoma. Methods: Before surgery, 30 patients with an indeterminate pulmonary nodule were intravenously administered a folate receptor-targeted fluorescent contrast agent specific for primary lung adenocarcinomas. During surgery, the nodule was removed and the presence of fluorescence (optical biopsy) was assessed in the operating room to determine if the nodule was a primary pulmonary adenocarcinoma. Standard-of-care frozen section and immunohistochemical staining on permanent sections were then performed as the gold standard to validate the results of the optical biopsy. Results: Optical biopsies identified 19 of 19 (100%) primary pulmonary adenocarcinomas. There were no false positive or false negative diagnoses. An optical biopsy required 2.4 minutes compared to 26.5 minutes for frozen section (P < 0.001) and it proved more accurate than frozen section in diagnosing lung adenocarcinomas. Conclusions: An optical biopsy has excellent positive predictive value for intraoperative diagnosis of primary lung adenocarcinomas. With refinement, this technology may prove to be an important supplement to standard pathology for examining close surgical margins, identifying lymph node involvement, and determining whether suspicious nodules are malignant.